1988
DOI: 10.1088/0031-9155/33/11/003
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the cavitational effects of clinical ultrasound by sonoluminescence: 2. Thresholds for sonoluminescence from a therapeutic ultrasound beam and the effect of temperature and duty cycle

Abstract: Sonoluminescence, produced when a therapeutic ultrasound generator operating at 1 MHz was used to insonate a tank of water, was detected using a photomultiplier tube and analysed using pulse height analysis. Spectra of the number of counts per second were obtained for the complete range of observed pulse heights, under exposure conditions similar to those used in clinical practice. Water containing different concentrations of dissolved gases and an agar solution were investigated during the course of the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…It is still controversial how temperature affects cavitational effects. Chendke and Fogler showed that sonoluminescence, a cavitational effect, was decreased as temperature increased in the range 11-89 • C using 20 KHz ultrasound sonicating to water [28], while Pickworth et al reported that, by also detecting sonoluminescence, the cavitation threshold decreased as temperature rose in the range 22-45 • C, using a 1 MHz continuous or pulsed ultrasound at intensities up to 3 W/cm 2 in water [29]. Recently, Entezari and Kruus showed that the effect of cavitation is dependent on temperature and ultrasound intensity.…”
Section: Discussionmentioning
confidence: 99%
“…It is still controversial how temperature affects cavitational effects. Chendke and Fogler showed that sonoluminescence, a cavitational effect, was decreased as temperature increased in the range 11-89 • C using 20 KHz ultrasound sonicating to water [28], while Pickworth et al reported that, by also detecting sonoluminescence, the cavitation threshold decreased as temperature rose in the range 22-45 • C, using a 1 MHz continuous or pulsed ultrasound at intensities up to 3 W/cm 2 in water [29]. Recently, Entezari and Kruus showed that the effect of cavitation is dependent on temperature and ultrasound intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Iernetti found a maximum at 12° C for aerated water. Pickworth et al [261] found that the sonoluminescence from areated water in a 1-MHz standing-wave field increased at both 1 and 3 W cm" 2 (/SATA) in the range 22-45° C. An experimental study of cavitation, rather than sonoluminescence, by Blake [262] showed that cavitation thresholds decrease with temperature in the range -10-50° C.…”
Section: Fii) Dependence Of Sonoluminescence On the Liquid The Sonolmentioning
confidence: 99%
“…In 1988, Pickworth et al [261] observed an interesting form of pulse enhancement when studying the distribution of energies of the sonoluminescent pulses as detected by a photomultiplication system connected to a pulse height analyser. The apparatus is shown in Figure 5.39.…”
Section: (E) Pulse Enhancement Through Bubble Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is not a surprise to expect light emission due to the high temperature releasing by transiently cavitating bubbles collapse, the precise mechanism of light production is still unclear. Sonoluminescence may be occurred due to the blackbody radiation, bremsstrahlung radiation, recombination radiation, or combinations thereof [19,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%